Oral Histories about the Famine of 1941-1945 as the Source of Knowledge of the Everyday Life of the Rural Population of the Ulyanovsk Area of Volga Region - M. G. Matlin (Научный диалог, 2018)
Based the analysis of narratives about hunger in the rear areas during the great Patriotic war some features of everyday life of rural population in the territory of the Ulyanovsk Area of Volga Region are analyzed. It is noted that the daily life of Russian female peasants is revealed mainly in memories. It is shown that, despite the extreme conditions of life and fundamental change in the composition of the family, everyday life of a woman included the same basic elements as during peacetime: obtaining and preparation of food, raising children, work on the garden plot, the maintenance of family and neighborly relations, the performance of labor and economic duties to the State, including the local authorities. However, as the author of the article emphasizes, the realities of wartime have transformed these components of everyday life significantly, prioritizing the development of a strategy of physical survival and, above all, the overcoming of hunger and its consequences. As is established by the analysis of narratives, that is why during wartime were the diet and those everyday life practices that had been developed by the Russian peasantry to overcome hunger in the XIX century and the first third of the XX century were revitalized. Thanks to the analysis of oral stories about hunger in 1941-1945 it became possible to reveal in detail the emotional and personal perception as well as experiences of Russian female peasants during the wartime. Like any study of everyday life, the analysis may significantly complement and change the historical knowledge of that time.